Uncovering the risks for driver injury severities for truck-trailer and passenger car crashes at highway-railroad crossings - Mouyid Islam; Asim Alogaili (Transportation Research Interdisciplinary Perspectives)
Highway-railroad crossings are critical intersections where the trajectory of trucks hauling trailers intersects with railway tracks. The coexistence of these large trucks and trains at these junctions poses inherent safety, health, and environmental risks for passenger cars, truck-trailers, trains, and highway-rail crossing infrastructures. Five years of US crash data were utilized to model driver injury severity using a mixed logit model with heterogeneity in means and variances, exploring the risk factors for passenger cars and truck-trailers at a grade crossing. The estimated model for truck-trailer and passenger car crashes at railroad crossings included factors, such as spatial variables, weather conditions, ambient lighting, vehicle maneuvers over the crossing, driver age and gender, gate operation characteristics, the location of warning signs, the type of crossing warning (including gates), the stopping position of the truck-trailer on the crossing, and the release of hazardous materials by rail equipment. These factors were found to influence different levels of driver injury severity. The marginal effects of the estimated models showed that crashes involving truck-trailers, particularly those at crossings in Texas, were more likely to result in higher driver fatalities compared to crashes involving passenger cars. These crashes were also more likely to occur when crossing warnings and highway signals were not interconnected, or when warnings were located on both sides of the crossing. Improving roadway infrastructure, especially by integrating highway signals with rail-grade crossing warnings, is one of the critical factors in enhancing safety. Additionally, education through truck driver training modules, outreach efforts, and enforcement to prevent vehicles from crossing the gates are critical for enhancing safety at rail-grade crossings.